Development of a Monitoring Plan for the Accidental Dispersal of Genetically Modified Oilseed Rape in Italy - Valentina Rastelli; Valeria Giovannelli; Giovanni Staiano; Pietro Massimiliano Bianco; Alfonso Sergio; Matteo Lener (Seeds)
This paper presents a pilot project conducted by ISPRA and ARPA Campania to develop a monitoring protocol to detect the presence of genetically modified (GM) oilseed rape (Brassica napus) plants resulting from accidental seed dispersal during transportation from entry points to storage and processing facilities; the project has been implemented in Italy’s Campania region. The unintentional dispersal of GM oilseed rape seeds and the potential establishment of feral populations have been identified as environmental concerns in various countries, even when GM oilseed rape is imported solely for processing and not for cultivation. The project activities were designed, taking into account the characteristics of the Italian environment and infrastructures. Multiple sampling campaigns were conducted in autumn 2018, spring 2019, and autumn 2019 to validate the selected transects and assess the presence of Brassicaceae species, with a particular focus on oilseed rape. These efforts involved direct monitoring and sample collection along transport routes from the port of Salerno to seed companies in the provinces of Benevento and Caserta. Field observations and import data revealed a decrease in oilseed rape movement at the port of Salerno in the years preceding the survey, while seed companies near Benevento remained active sites for white mustard (Sinapis alba). The presence of S. alba and the simultaneous occurrence of oilseed rape and Raphanus raphanistrum—a species with high hybridization potential—support the hypothesis that seed companies may act as hotspots for accidental seed dispersal and that potential interspecific gene flow can occur. The study also validated the adopted sampling and molecular analysis methods, including DNA extraction and PCR, for the detection of the Cruciferin A (CruA) gene in all Brassica species collected. These findings highlight the need to strengthen post-marketing monitoring plans, even when GM rapeseed is imported solely for processing, to mitigate the potential risks associated with unintended gene flow.